RANCANG BANGUN GENERATOR SINYAL FISIOLOGIS EMG JARI KELINGKING DAN EOG MATA BERBASIS ARDUINO NANO - Rachmat, Hendi Handian; Firdaus, Muhammad M.; Hernawan, Allyfa N.; Septiani, Sindi (Jurnal Media Elektro, 2025)
In this study, the design and implementation of a portable Arduino Nano-based physiological signal generator for pinky EMG and EOG eye movement (looking right and left) were carried out. The purpose of this study is to develop a device capable of storing and generating physiological signals, so that the device can serve as a substitute for test subjects. The physiological signal generator system was implemented by storing digital physiological signal data from test subjects in the internal memory of the Arduino Nano microcontroller, which also acts as the system's controller and processor. The signal conditioning system uses an MCP4725 module 12-bit resolution DAC, an LM358 OP-Amp as a non-inverting signal amplifier, a 20x4 LCD as the signal menu display, and a joystick module for selecting signal menus. The system was tested by comparing the signals generated by the signal generator with the physiological signal data recorded from test subjects (the data stored on the device). Based on the test results, the signal generated by the electronic device is visually ±100% identical to the recorded physiological signal data. The average amplitude difference is relatively small, with the smallest difference being 0.1 mV and the largest difference being 4.9 mV.